Combining functional magnetic resonance imaging with transcranial electrical stimulation - Saiote, Catarina; Turi, Zsolt; Paulus, Walter; Antal, Andrea (Frontiers in Human Neuroscience, 2013)
Transcranial electrical stimulation (tES) is a neuromodulatory method with promising potential for basic research and as a therapeutic tool. The most explored type of tES is transcranial direct current stimulation (tDCS), but also transcranial alternating current stimulation (tACS) and transcranial random noise stimulation (tRNS) have been shown to affect cortical excitability, behavioral performance and brain activity. Although providing indirect measure of brain activity, functional magnetic resonance imaging (fMRI) can tell us more about the global effects of stimulation in the whole brain and what is more, on how it modulates functional interactions between brain regions, complementing what is known from electrophysiological methods such as measurement of motor evoked potentials. With this review, we aim to present the studies that have combined these techniques, the current approaches and discuss the results obtained so far.